Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
L-9-3 July 20, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Outer end. In background, south side of this fjord, which is formed by Ymer Island and very large iceberg in foreground, was just west of and near Cape Graah. Photo taken from motor-boat looking S.E.